A 'Triple Bottom Line' Approach to Advanced Project Evaluation - Ding, Grace K. C. (Cambridge Scholars Publishing, 2020)
The concept of 'the triple bottom line' has recently emerged to describe a new framework for development aimed at achieving economic and social balance while maintaining the long-term integrity of ecological systems. This requires measuring not only the economic viability of projects, but also their impact on the environment and their contribution to society. We live in a world where most people are aware of the importance of our environment. The way in which this realisation came about has, in hindsight, not been as simple as could have been expected. Systematic evaluations of the economic vi.